OpenStudy (anonymous):

4(x - 3) - 5(x + 1) = 3 Which statement shows a correct next step in solving the equation? The equation can become 4x - 3 - 5x + 1 = 3 by applying the associative property of multiplication. The equation can become 4x - 3 - 5x + 1 = 3 by applying the distributive property. The equation can become 4x - 12 - 5x - 5 = 3 by applying the distributive property. The equation can become 4x - 12 - 5x - 5 = 3 by applying the associative property of multiplication.

3 years ago
OpenStudy (anonymous):

@hyntc @Baseballa101

3 years ago
OpenStudy (anonymous):

The equation can become 4x - 12 - 5x - 5 = 3 by applying the distributive property.

3 years ago
Similar Questions: